Land use and land tenure patterns in the Windward Islands : an analysis of the agricultural sectors of Martinique, St. Vincent and the Grenadines, St. Lucia, Dominica and Grenada 1970-1990 - Crichlow, Michaeline (CNIRD St. AugustineTT, 1994)
Investigates the patterns of land use and land tenure systems which have emerged and have been inplemented over the period 1970-1990.